Slope, grain size, and roughness controls on dry sediment transport and storage on steep hillslopes. Issue 4 (20th April 2017) - DiBiase, Roman A.; Lamb, Michael P.; Ganti, Vamsi; Booth, Adam M.
Abstract: Existing hillslope sediment transport models developed for low‐relief, soil‐mantled landscapes are poorly suited to explain the coupling between steep rocky hillslopes and headwater channels. Here we address this knowledge gap using a series of field and numerical experiments to inform a particle‐based model of sediment transport by dry ravel—a mechanism of granular transport characteristic of steep hillslopes. We find that particle travel distance increases as a function of the ratio of particle diameter to fine‐scale (<1 m) topographic roughness, in agreement with prior laboratory and field experiments. Contrary to models that assume a fixed critical slope, the particle‐based model predicts a broad transition as hillslopes steepen from grain‐scale to hillslope‐scale mean particle travel distances due to the trapping of sediment on slopes more than threefold steeper than the average friction slope. This transition is further broadened by higher macroscale (>1 m) topographic variability associated with rocky landscapes. Applying a 2‐D dry‐ravel‐routing model to lidar‐derived surface topography, we show how spatial patterns of local and nonlocal transport control connectivity between hillslopes and steep headwater channels that generate debris flows through failure of ravel‐filled channels following wildfire. Our results corroborate field observations of a patchy transition from soil‐mantled to bedrock landscapes and suggest that there is a dynamic interplay between sediment storage, roughness, grain sorting, and transport even on hillslopes that well exceed the angle of repose. Key Points: Sediment transport on steep hillslopes is sensitive to grain size and topographic roughness The transition from local to purely nonlocal transport is broad due to topographic roughness A new 2‐D ravel‐routing model captures the spatial patterns in deposition and nonlocal transport